"One in all and all in one" : zero waste clothing transformable - Broega, A. C. (2012)
“One in All and All in One” is the model of a garment that arises in the course of an investigation on sustainability in clothing. The Project is designed and modeled on a "Rethink Design" methodology and it is directed to the multi-functionality and to the zero waste plans. It covers relevant requirements ranging from the conscious consumption until the rationalization of costs and accumulation of rejected or discarded goods. It is an example of a durable product, adaptable to different functionalities and occasions and without the complexity has associated with transformable clothing, being one of the found solutions to reduce the fashion products obsolescence, usually marketed in fast and short cycles.